2020
DOI: 10.1002/joc.6714
|View full text |Cite
|
Sign up to set email alerts
|

Representation of the Indian Ocean Walker circulation in climate models and links to Kenyan rainfall

Abstract: Reliable climate change projections over East Africa are vital because of regional vulnerability to precipitation changes. However, global climate models from Coupled Model Intercomparison Project Phase 5 (CMIP5) display significant biases in their representation of key East African rainfall seasons, which call into question the reliability of projected climate change. We investigate the links between models' representation of rainfall over Kenya during the long and short rains and the proximate Walker circula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 80 publications
5
40
0
Order By: Relevance
“…The previous section has demonstrated that CMIP5 model projections, which are generally toward a wetter East Africa, occur concomitantly with changes to the IOWC including reduced positive omega and enhanced easterly winds. This supports other recent studies arguing that the IOWC is an important control on East African rainfall in both observations and models; it has been suggested that the dynamics control rainfall rather than the other way around (e.g., Chadwick et al, 2013;King et al, 2020;Mutai & Ward, 2000;Nicholson, 2017;Williams & Funk, 2011;Zhao & Cook, 2021), especially given the important role of SST in IOWC variability (Black, 2005;Hoell et al, 2017;Hoell & Funk, 2014;Liebmann et al, 2014). The important task that follows from this analysis is to assess the plausibility of these future projections in the context of the models' known biases in representation of the historical IOWC and associated rainfall conditions.…”
Section: Links Between Historical Biases and Future Projections Of Iowc Variablessupporting
confidence: 90%
See 4 more Smart Citations
“…The previous section has demonstrated that CMIP5 model projections, which are generally toward a wetter East Africa, occur concomitantly with changes to the IOWC including reduced positive omega and enhanced easterly winds. This supports other recent studies arguing that the IOWC is an important control on East African rainfall in both observations and models; it has been suggested that the dynamics control rainfall rather than the other way around (e.g., Chadwick et al, 2013;King et al, 2020;Mutai & Ward, 2000;Nicholson, 2017;Williams & Funk, 2011;Zhao & Cook, 2021), especially given the important role of SST in IOWC variability (Black, 2005;Hoell et al, 2017;Hoell & Funk, 2014;Liebmann et al, 2014). The important task that follows from this analysis is to assess the plausibility of these future projections in the context of the models' known biases in representation of the historical IOWC and associated rainfall conditions.…”
Section: Links Between Historical Biases and Future Projections Of Iowc Variablessupporting
confidence: 90%
“…Therefore, the ensemble mean rainfall averages for both historical and future simulations of the long rains are thus dominated by a few very wet or very dry models. The wet biased models in MAM could be considered more realistic, as the ensemble mean has a dry bias during the season, but King et al (2020) have shown that these highly biased models have unrealistic dynamics over East Africa and the tropical Indian Ocean in the historical coupled simulations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations